Two-dimensional mapping of the electric field distribution inside vacuum microgaps observed in a scanning electron microscope. (January 2019) - Meng, Guodong; Dong, Chengye; Gao, Xinyu; Zhang, Dujiao; Wang, Kejing; Zhang, Pengcheng; Cheng, Yonghong
Abstract: In this paper, we present an in-situ measurement method to directly observe the distribution of the local electric field between vacuum microgaps. The measurement was performed in-situ inside a high resolution scanning electron microscope (SEM), and the nature of the local electric field was characterized through secondary electron contrast images with the aid of Rutherford scattering theory. Based on the regular fringes in these contrast images, the distribution of the local electric field could be extracted from the contour lines of the fringes while the magnitude of the local electric field could be evaluated qualitatively by the gradient of the contour lines. The finite element method (FEM) simulation and the three-electrodes imaging experiment were also conducted, and the obtained two-dimensional electric field distribution agreed well with the FEM simulation, suggesting that the in-situ visualization technique could be useful for determining the local field enhancement behavior for various geometrical configurations and microscale structures. A physical mechanism for the local electric field mapping is suggested. This study demonstrates the potential of SEM imaging for obtaining information about the local electric field within microelectronic structures and devices.